World Institute of Kimchi as a leading global institute of fermented foods. Issue 7 (21st June 2013) - Kim, Eun‐Young
<x xml:space="preserve">Abstract</x> "Kimchi" is a world famous fermentated food originating from Korean cuisine. It has many health benefits and in order to systematically understand kimchi, the Korean government has set up the World Institute of Kimchi (WIKIM) – read more about kimchi and WIKIM in this forum article. (Image © WIKIM) <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>